Inovasi Perkuliahan Sejarah Sastra Indonesia dengan Menggunakan Metode Diskusi Kelompok Model Kepala Bernomor - Yenni Hayati (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
To make the class activities effective, creative and fun innovation in teaching and learning process is required. One innovation that can be done is the use of numbered heads in a group discussion model. This method allows students to be actively and creatively involved in the activities, so the teaching process can be more interesting for students. This method also causes the students more responsible in doing the task in groups. Key words: Innovation, lecture, numbered head together